Agri-digital innovation and technology: Supporting trade and social safety for agriculture sector - Hassan, Islam (2021)
IFPRI Egypt Seminar Series provides a platform for all people striving to identify and implement evidence-based policy solutions that sustainably reduce poverty and end hunger and malnutrition. The series is part of the United States Agency for International Development (USAID) funded project called “Evaluating Impact and Building Capacity” (EIBC) that is implemented by IFPRI.